MACIEJEWSKI'S 'METHOD' - KACZMAREK, WOJCIECH (Colloquia Litteraria, 2018)
The article analyses kerygmatic method of interpretation that was first employed in literary studies by professor Marian Maciejewski. Thanks to this method one can verify a text and its relation to Christianity. Kerygmatic method calls for objective preciseness in defining the level of religiosity of a given text, regardless of whether it was inspired by Christianity or natural religiosity. Maciejewski’s research, mainly his works on Mickiewicz’s poems, is still governed by the directives of historical-literary analysis, nevertheless he considers his observations within the dynamics of Christian life and not in a perspective of vaguely undefined religiosity.